HBV-infection rate and long-term outcome after liver-transplantation of anti-HBc-positive liver-grafts to HBV-naïve recipients: a retrospective study - Hornuß, Daniel; Rudi, Anna; Koerner, Lucas; Mohr, Isabelle; Merle, Uta; Wehling, Cyrill; Rupp, Christian; Dill, Michael T.; Golriz, Mohammad; Schnitzler, Paul; Brenner, Thorsten; Mehrabi, Arianeb; et al. (Clinics and research in hepatology and gastroenterology, 2021)
Background - Anti-HBc only positive liver grafts may be suitable for HBV-naive recipients insofar as an appropriate infection prophylaxis is performed. Therefore, we investigated the effect of prophylactic regimens on HBV infection prevention and long-term outcome of anti-HBc-positive graft recipients. - Patients and methods - This retrospective monocenter study consisted of a cohort of 1912 patients who underwent deceased donor liver transplantation at our transplant center between June 1987 and July 2019. 81 HBV-naïve patients after reception of an anti-HBc-positive liver-graft and consecutive HBV prophylaxis were selected for further examination. HBV infection rate and host- and graft-survival rates were compared to a matched control group consisting of 162 HBV-naïve patients after reception of anti-HBc-negative grafts. Pharmaceutical HBV prophylaxis included: only HBIG, only NUCs, or combined HBIG and NUCs. - Results - Compared to control cases of HBV-naïve anti-HBc-negative graft recipients, no differences in host- and graft-survival rate were determined.13 of 81 anti-HBc-positive graft recipients (16%) developed HBV-infection after liver transplantation. No patient suffered from HBV infection after receiving modern NUCs. Survival analysis showed no statistical differences between patients with and without infection concerning host- and graft-survival. - Conclusion - Especially in times of organ shortage, anti-HBc-positive liver grafts may be useful for liver transplantation in HBV-naïve recipients. Efficient prophylactic regimens can prevent HBV-infection.